Between Rack Rents and Paternalism: Economic Behaviour and the Lease Market in Westphalia, with a Particular Focus on the 19th Century - Bracht Johannes; Scholten-Buschhoff Friederike (Jahrbuch für Wirtschaftsgeschichte, 2022)
Departing from research on Westphalian leases between 1600 and 1900 the paper discusses the lease market of and price determination on three Westphalian estates. While economic history approaches suppose that leases can be seen as market relations and are therefore useful indicators to measure agricultural productivity, a more anthropological perspective emphasises the social relations between lessor (here: noble estate owner) and leaseholders. The choice of an adequate perspective has significant implications for research on agricultural productivity based on rents and leases. Our results indicate that the contractual arrangement of leasehold (well defined duration, announcement, auctions) was used to achieve the highest possible leases. However, at least until the 1830s, demand for leasehold land was rather low and leaseholders could benefit from a lack of competition. Price determination of leases resulted in rents below the Ricardian rent. Therefore, we argue that important assumptions of the established price approach, which uses leases as proxies for productivity, are not met and the analysis of agricultural productivity requires additional evidence on the leaseholder’s income and profit.